Utilization of Waste Crab Shell (Scylla serrata) as a Catalyst in Palm Olein Transesterification - Gaanty Pragas, Maniam; Boey, Peng Lim; Shafida, Abd Hamid (Japan Oil Chemists' Society, 2009)
Aquaculture activity has increased the population of crab, hence increasing the generation of related wastes, particularly the shell. In addition, the number of molting process in crabs compounds further the amount of waste shell generated. As such, in the present work, the application of the waste crab shell as a source of CaO in transesterification of palm olein to biodiesel (methyl ester) was investigated. Preliminary XRD results revealed that thermally activated crab shell contains mainly CaO. Parametric study has been investigated and optimal conditions were found to be methanol/oil mass ratio, 0.5:1; catalyst amount, 4 wt.%; and reaction temperature, 338 K. As compared to laboratory CaO, the catalyst from waste crab shell performs well. thus creating another low-cost catalyst source for producing biodiesel as well as adding value to the waste crab shell. Reusability of crab shell CaO has also been studied and the outcome confirmed that the catalyst is capable to be reutilized up to 11 times, without any major deterioration.